2000
DOI: 10.1002/1096-9098(200007)74:3<223::aid-jso14>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Celsite® port and catheter as an intraperitoneal access device in the treatment of ovarian cancer

Abstract: Background and Objectives:In ovarian cancer, development of safe and effective methods for providing long-term access to the peritoneal cavity has become increasingly important. Methods: A modified Port-A-Cath (Celsite-port and catheters, B. Braun, Chasseneuil, France) was used in 56 patients with presumed epithelial ovarian cancer at the conclusion of primary or second-look laparotomy. In 37 patients, ports were located on the right costal margin in the midclavicular region and in 19 in the xiphoid region. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Clinical characteristics of 11 included papers [10][11][12][13][14][15][16][17][18][19][20], associated with our case report, were summarized (total case n=14) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical characteristics of 11 included papers [10][11][12][13][14][15][16][17][18][19][20], associated with our case report, were summarized (total case n=14) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In case complications related to the peritoneal port occur the treating physician should be informed, discuss the problem with the study team, and handle in the patient’s best medical interest. Previous studies that administrated intraperitoneal chemotherapy reported problems like catheter obstruction, port dysfunction, infection, and abdominal pain during administration of chemotherapy 43–45. In certain cases the peritoneal port might have to be replaced to continue treatment, in others cases patients might have to discontinue study participation.…”
Section: Methods and Analysismentioning
confidence: 99%
“…In GOG 172, intraperitoneal treatment (intravenous paclitaxel 135 mg/m 2 on day 1, intraperitoneal cisplatin 100 mg/m 2 on day 2 and intraperitoneal paclitaxel 60 mg/m 2 on day 8) resulted in significantly worse neurotoxicity compared with pure intravenous therapy, at 3–6 weeks and at one year after the completion of chemotherapy. If intolerable peripheral neuropathy develops, switching to intravenous carboplatin with intravenous docetaxel is an option. Abdominal pain is worse with intraperitoneal therapy compared with intravenous treatment alone, although it appears to be transient, related to stretching and distension of bowel‐to‐bowel adhesions from the volume of fluid instilled.…”
Section: Intraperitoneal Chemotherapy For Optimally Debulked (<1 Cm) mentioning
confidence: 99%
“…Abdominal pain is worse with intraperitoneal therapy compared with intravenous treatment alone, although it appears to be transient, related to stretching and distension of bowel‐to‐bowel adhesions from the volume of fluid instilled. Some patients experience discomfort related to abdominal distension or from intercostal nerve irritation …”
Section: Intraperitoneal Chemotherapy For Optimally Debulked (<1 Cm) mentioning
confidence: 99%